Aplikasi Kasir Berbasis Web untuk Efisiensi Transaksi di Clean Laundry - Ade Herliana; Felix; Muhammad Hasbi Noor; Wasis Haryono (Journal Of Informatics And Busisnes, 2024)
This research presents the development of a web-based cashier application aimed at enhancing transaction efficiency at Clean Laundry. The growing demand for laundry services necessitates the implementation of an integrated system to manage transactions effectively. The application is designed to facilitate various functions, including order processing, payment management, and customer record maintenance, thereby minimizing manual errors and reducing transaction times. By utilizing modern web technologies, the application provides an intuitive user interface that allows staff to navigate easily and perform tasks swiftly.